STUDI KOMPARATIF HASIL BELAJAR PKn DAN BAHASA SUNDA MELALUI MODEL TGT PADA SISWA SEKOLAH DASAR - Safitri, Ika; Nabila Al-Adzillah; Mayang Widaningsih; Ina Setiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was designed to examine and compare learning achievement in Civics (PKn) and Sundanese Language among grade IV students of SDN 4 Awirarangan, Kuningan Regency, Academic Year 2025/2026, following the application of the Team Games Tournament (TGT) cooperative learning model. TGT was chosen because its group-based competitive structure is considered capable of promoting greater student involvement in learning. The study adopted a quantitative approach with a one-group post-test only design involving 21 students as research participants. Data collection was carried out using validated post-test instruments, which were subsequently analyzed through descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank test. Findings revealed a mean score of 60.95 for Civics (38.1% passing rate) and 67.62 for Sundanese Language (71.4% passing rate). Despite this descriptive gap, the Wilcoxon test produced Z = -1.288 with a significance level of 0.198 > 0.05, indicating that H₀ was retained. Accordingly, no statistically significant difference was found between student learning outcomes in the two subjects under the TGT model. These results point to TGT’s potential as a cross-disciplinary instructional approach whose effectiveness is shaped by contextual variables including content difficulty and student readiness. Keywords: learning outcomes, TGT model, Civics, Sundanese Language, elementary school